Analysis on Fractal-Permeability Characteristics of Construction Waste Filling Body in Gob - Gao, Zhongguo; Xin, Yajun; Zhang, Dongying; Li, Huan; Chen, Zhuguo; Wang, Xiaopeng; Li, Guangzeng; Ji, Hongying (International Journal of Materials Science and Technology Studies, 2024)
The mine application of construction waste permeability filling body is an effective way to avoid the collapse of overlying rock strata caused by coal mining, to solve the questions of surface resource occupation and pollute the ecological environment, and to promote regional hydrogeological balance. Based on the infiltration test on twelve groups of non-cemented and cemented samples with different particle size ratio, the variation characteristics of permeability coefficient of non-cemented and cemented construction waste samples with different fine content and cement were analyzed. The porosity of non-cemented samples and cemented ones was obtained, the relationships of fine content and porosity, permeability coefficient were analyzed, the relationships of fractal dimension and porosity, permeability coefficient on non-cemented samples and cemented ones were discussed. The results showed that fine content was negatively correlated to the permeability coefficient of non-cemented samples and non-cemented ones. The porosity decreased with fine content increasing, the porosity of non-cemented samples ranged from 5.007 7.029%, and the one of cemented samples was 3.230 6.508%. Fractal dimension of non-cemented samples and cemented ones were fine aggregate> medium coarse aggregate> coarse aggregate, and the fractal dimension of non-cemented samples was less than the cemented ones, the porosity and the mass fractal dimension could well represent the relationship between the permeability and fine content.